Model Pemberdayaan Kader Lingkungan Adiwiyata dalam Pengelolaan Limbah Organik di SMPN 39 Semarang - Nadia Nadia; Syifa Amalia Geanti Cahyani; Ariq Dwi Yulian Nugroho; Elsha Pipit Nathalia; Muhammad Azra Fikri Maulana; Fathul Khoeriyah; Devia Fitri Alfiana; Hanif Syifa Ifada (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The main problem in the environment today is the large amount of organic waste produced from daily activities that is not managed properly, such as citrus fruit waste and fish waste. This can have a bad impact if not handled properly. This research aims to explain the process of implementing empowerment in organic waste management at SMP Negeri 39 Semarang, with a focus on making aromatherapy candles and organic liquid fertilizer. The Participatory Action Research (PAR) method is used to involve active participation of Adiwiyata Cadre students in research and action, enabling them to not only be research subjects but also actors in implementing community-based solutions. The research results show that the PAR method is able to provide students with an in-depth understanding of the importance of waste management. This process enriches students' knowledge of recycling and has a direct impact on the school environment, enabling them to face future environmental challenges.